PSYCHOLOGICAL PEDAGOGICAL FACTORS OF ENSURING THE CONTENT OF THE STUDENTS’ EDUCATIONAL ACTIVITY AND SUCCESS IN THE EDUCATIONAL ACTIVITY - Shakhnoza Gapparovna Ibragimova (Galaxy International Interdisciplinary Research Journal, 2022)
In the article, the content of students’ educational activities and pedagogical-psychological factors in ensuring success in educational activities and their essence, based on research, are covered.